2018
DOI: 10.12707/riv17080
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Wagnild and Young’s Resilience Scale in adolescents in residential care

Abstract: Background: Residential care can protect adolescents by developing and maintaining their resilience. Objective: To validate the Resilience Scale (RS), developed by Wagnild and Young (1993) and adapted to the Portuguese population by Felgueiras, Festas, and Vieira (2010), in a sample of adolescents in residential care. Methodology: Methodological study on the validation of the RS, following a previous Portuguese adaptation, in a sample of 384 adolescents in residential care. Results: The 25-item RS had a high i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
(19 reference statements)
1
2
1
Order By: Relevance
“…In this study, girls also had a higher mean level of resilience than boys. These results are contrary to those found in another study conducted in Portugal, where boys had higher mean levels of resilience (Gonçalves & Camarneiro, 2018). However, they are consistent with another study where adolescents with another type of chronic illness (leukemia) were more resilient (Pars & Çavusoglu, 2019).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In this study, girls also had a higher mean level of resilience than boys. These results are contrary to those found in another study conducted in Portugal, where boys had higher mean levels of resilience (Gonçalves & Camarneiro, 2018). However, they are consistent with another study where adolescents with another type of chronic illness (leukemia) were more resilient (Pars & Çavusoglu, 2019).…”
Section: Discussionsupporting
confidence: 58%
“…The results obtained in Study II demonstrated that the levels of resilience in adolescents with chronic illness are sufficient and higher than those found in other studies carried out in Portugal (Felgueiras et al, 2010;Gonçalves & Camarneiro, 2018). However, the differences may be due to the small size of this sample when compared to the other samples (215 and 384), but also because none of the previous studies focused on adolescents with chronic illness, but rather on adolescents in school and residential childcare settings.…”
Section: Discussioncontrasting
confidence: 55%
“…Similar results were reported by Rodríguez (2021), where the average was 138.7, and Caldera- Montes et al (2016) in Mexico, where the average was 144.6. A Portuguese study reported a mean of 129.4, which is lower than the results found in the aforementioned studies (Gonçalves & Camarneiro, 2018). This is how both high (Ordoñez Morales, 2020) and medium (Mejía, 2018) levels of resilience have been reported in university students despite adversity such as the pandemic.…”
Section: Discussionmentioning
confidence: 75%
“…No other study has been found that has tested the factor structure in such a sample and environment. Indeed, the RS has been used in younger participants [45][46][47][48][49][50][51] although it was developed using older women [2,3]. Moreover, measurement instruments related to resilience are under-researched in settings such as ART [9,20,21,52], and this study expresses the utility of the RS in reproductive care as it facilitates the assessment of the impact of infertility and ART on being resilient and coping with such adversity.…”
Section: Discussionmentioning
confidence: 99%